2020
DOI: 10.1007/s00737-020-01050-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with re-initiation of antidepressant treatment following discontinuation during pregnancy: a register-based cohort study

Abstract: Antidepressant treatment when facing a pregnancy is an important issue for many women and their physicians. We hypothesized that women with a greater burden of pre-pregnancy psychiatric illness would be more likely to re-initiate antidepressants following discontinuation of treatment during pregnancy. A register-based cohort study was carried out including 38,595 women who gave birth between the 1st of January 2007 and the 31st of December 2014, who had filled a prescription for an antidepressant medication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(53 reference statements)
3
6
0
Order By: Relevance
“…Another study examined pregnant women with depression diagnosis and receipt of antidepressant within 6 months pre-conception in Korea, and revealed that 95% of the cohort terminated treatment during pregnancy (Noh et al, 2022). Consistent with several previous studies investigating the relationship between maternal characteristics and prenatal antidepressant continuation (Donald et al, 2021; Hurault-Delarue et al, 2019; Molenaar et al, 2020b; Noh et al, 2022; Petersen et al, 2011; Wikman et al, 2020), our findings demonstrated that older age at conception (⩾35 years), more recent calendar year of delivery and proxies for greater illness severity were significantly associated with antidepressant continuation. In fact, some recent reports also noticed a change in prescribing practice toward continuation of antidepressant during pregnancy over the years (Molenaar et al, 2020b; Wikman et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another study examined pregnant women with depression diagnosis and receipt of antidepressant within 6 months pre-conception in Korea, and revealed that 95% of the cohort terminated treatment during pregnancy (Noh et al, 2022). Consistent with several previous studies investigating the relationship between maternal characteristics and prenatal antidepressant continuation (Donald et al, 2021; Hurault-Delarue et al, 2019; Molenaar et al, 2020b; Noh et al, 2022; Petersen et al, 2011; Wikman et al, 2020), our findings demonstrated that older age at conception (⩾35 years), more recent calendar year of delivery and proxies for greater illness severity were significantly associated with antidepressant continuation. In fact, some recent reports also noticed a change in prescribing practice toward continuation of antidepressant during pregnancy over the years (Molenaar et al, 2020b; Wikman et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…To determine factors associated with continuation of antidepressants into the second trimester, an array of maternal variables was selected a priori for analysis based on findings of prior literature suggesting that age (Donald et al, 2021; Hurault-Delarue et al, 2019; Petersen et al, 2011), year of delivery (Molenaar et al, 2020b; Wikman et al, 2020), parity (Molenaar et al, 2020b), chronic physical diseases (Hurault-Delarue et al, 2019) and proxies of psychiatric illness severity (Hurault-Delarue et al, 2019; Molenaar et al, 2020b; Noh et al, 2022; Petersen et al, 2011; Wikman et al, 2020) may predict continued treatment during pregnancy. The selected variables included age at conception, calendar year of delivery, parity, physical diseases as measured by Charlson Comorbidity Index (CCI; Charlson et al, 1987; Deyo et al, 1992), pre-existing depression and anxiety disorders, other pre-existing psychiatric disorders, substance and alcohol use disorders, history of psychiatric admission within 24 months before pregnancy, cumulative antidepressant use ⩾90 days within 12–3 months pre-pregnancy, use of antipsychotics, use of mood stabilizers, and use of sedatives and hypnotics (see Supplementary Material Table S1) in 12 months pre-pregnancy, as defined by having at least one prescription of the specified psychotropics during that period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with treatment resumption for pregnant women in Sweden are: a greater burden of pre-pregnancy psychiatric illnesses, multipara, higher educational level and have been born in the Nordic countries or the EU. Difference in severity of the psychiatric illness prior to pregnancy could explain the divergent results in the studies above (85). Among those continuing with antidepressants, however studies have shown that the overall rate of adherence to the medication varies between 60 and 86% (86,87).…”
Section: Antidepressant Medication During Pregnancymentioning
confidence: 97%
“…The women who discontinue their medication have a higher risk of relapsing during pregnancy compared with women who maintained their antidepressant medication (4,78,82). Discontinuation of antidepressant medication during pregnancy leads to treatment resumption in 12-57% of the cases before childbirth (75,(83)(84)(85). Factors associated with treatment resumption for pregnant women in Sweden are: a greater burden of pre-pregnancy psychiatric illnesses, multipara, higher educational level and have been born in the Nordic countries or the EU.…”
Section: Antidepressant Medication During Pregnancymentioning
confidence: 99%